2021
DOI: 10.1109/tbme.2021.3053463
|View full text |Cite
|
Sign up to set email alerts
|

Model Selection Based Algorithm in Neonatal Chest EIT

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Both the absolute values and the location of the silent spaces were different among three different models in almost every studied subject (table 1). This coincided with the findings that the effect of improper chest model selection may be huge (Seifnaraghi et al 2021) and the information derived from such inappropriately calculated silent spaces may be deceiving. Therefore, the results suggested that the subjectspecific meshes and lung contours may be needed.…”
Section: Discussionsupporting
confidence: 75%
“…Both the absolute values and the location of the silent spaces were different among three different models in almost every studied subject (table 1). This coincided with the findings that the effect of improper chest model selection may be huge (Seifnaraghi et al 2021) and the information derived from such inappropriately calculated silent spaces may be deceiving. Therefore, the results suggested that the subjectspecific meshes and lung contours may be needed.…”
Section: Discussionsupporting
confidence: 75%
“…The fitted trapezoid was further rounded with a radius corresponding to 25% of its height at all corners. The impact of using inaccurate existing models on clinically important parameters in lung monitoring is detailed in [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with previous model-based methods [39,40], there are two alternatives for training the network: end-to-end training of the complete system consisting of k max blocks, or sequential training of each block. Nevertheless, for our scenario, conducting end-toend training is not feasible because of two primary factors.…”
Section: Graph Convolutional Neural Networkmentioning
confidence: 99%